Spatial and Temporal Dynamics of Dissolved Oxygen Concentrations and Bioactivity in the Hyporheic Zone. Issue 3 (23rd March 2018) - Reeder, W. Jeffery; Quick, Annika M.; Farrell, Tiffany B.; Benner, Shawn G.; Feris, Kevin P.; Tonina, Daniele
Abstract: Dissolved oxygen (DO) concentrations and consumption rates are primary indicators of heterotrophic respiration and redox conditions in the hyporheic zone (HZ). Due to the complexity of hyporheic flow and interactions between hyporheic hydraulics and the biogeochemical processes, a detailed, mechanistic, and predictive understanding of the biogeochemical activity in the HZ has not yet been developed. Previous studies of microbial activity in the HZ have treated the metabolic DO consumption rate constant (KDO ) as a temporally fixed and spatially homogeneous property that is determined primarily by the concentration of bioavailable carbon. These studies have generally treated bioactivity as temporally steady state, failing to capture the temporal dynamics of a changeable system. We demonstrate that hyporheic hydraulics controls rate constants in a hyporheic system that is relatively abundant in bioavailable carbon, such that KDO is a linear function of the local downwelling flux. We further demonstrate that, for triangular dunes, the downwelling velocities are lognormally distributed, as are the KDO values. By comparing measured and modeled DO profiles, we demonstrate that treating KDO as a function of the downwelling flux yields a significant improvement in the accuracy of predicted DO profiles. Additionally, our results demonstrate the temporal effect of carbon consumption on microbial respiration rates. Plain Language Summary: Dissolved oxygen concentrations and consumption rates are primary indicators of microbial respiration and redox conditions in streambed sediments. The traditional view of streambed microbial activity has treated the metabolic respiration rates as a temporally fixed and spatially homogeneous property that is determined primarily by the concentration of bioavailable carbon. However, our research shows that microbial respiration rates are both spatially and temporally variable. Spatial variability is driven by subsurface hydraulics, such that the respiration rate constant is a linear function of local subsurface flow velocities. For triangular dune type bedforms, subsurface flow velocities are lognormally distributed as are the respiration rate constants. Temporal variability is controlled by the abundance of bioavailable carbon. Key Points: Hyporheic hydraulics exert primary control over the functionality of the microbial communities that reside within the hyporheic zone The respiration rate, for microbes in the hyporheic zone, is a linear function of the local downwelling velocity Reaction rate constants are variable spatially proportionally to dowelling velocity and temporally to carbon availability